A COMPARATIVE STUDY ON THE FUNCTIONAL OUTCOME OF INTERTROCHANTERIC FRACTURES TREATED BY PROXIMAL FEMORAL NAILING OR DYNAMIC HIP SCREW FIXATION IN ELDERLY - Salgaonkar, Abhishek; Ganesh M T (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background Hip fracture is common among the elderly, particularly as a result of weak bones and falls. They tend to result in mobility and loss of independence. Objective: The paper will compare two forms of surgery Proximal Femur Nailing (PFN) and Dynamic Hip Screw (DHS) in order to determine which one produces a better recovery. Methods: There were 96 patients above 60 years old. They were separated into two categories one of which was treated with PFN and other one was treated with DHS. Harris hip score (HHS) was used to check their hip functioning at 1, 3, and 6 months. The rate at which the bone healed was viewed through x-rays. Findings: Patients that underwent PFN had improved bone healing and hip motions as compared to those that underwent DHS. PFN had less complications. Conclusion: PFN is more suitable in case of unstable fractures as it provides more stability and quicker healing whereas DHS is more effective in case of stable fractures.